ANALISIS PENGGUNAAN CAMPUR KODE PADA MAHASISWA UNIVERSITAS PELITA HARAPAN SEBAGAI IMPLIKASI DARI XENOGLOSOFILIA [ANALYSIS ON STUDENTS' USE OF CODE-MIXING THROUGH WHATSAPP AND EMAIL MESSAGES AS AN IMPLICATION OF XENOGLOSSOPHILIA] - Jonter Pandapotan Sitorus (Polyglot: Jurnal Ilmiah)
Language contact is one of the reasons for one's language variety or variation. The use of variation will also depend on the language attitude, whether it is included in a positive or negative language attitude toward a language. One of the languages in question is Indonesian, which is often mixed with words from foreign languages, especially English, thus violating the language codes of the variety used. This is known as code mixing. This study uses a survey method to find out the language attitudes of students at one of the private universities in Tangerang towards Indonesian and an observation method through the Simak Libat Cakap (SLC) technique to analyze the forms of student code-mixing. Based on the study's results, students still maintain a positive attitude towards the language, as evidenced by their pride in the Indonesian language. The findings of code mix used, such as the words text, quiz, error, submit, online class, upload, join, and others. Thus, from the results of the analysis of the forms of student code mix, it is evident that the phenomenon of xenoglossophilia occurs.